Fuzzy filtering based on decentralized adaptive event-triggered scheme for networked interconnected systems. Issue 13 (September 2021) - Xiang, Yun; Lin, Chong; Chen, Bing; Wang, Qing-Guo
Abstract: This paper focuses on the problem of the fuzzy filtering for networked nonlinear interconnected systems based on decentralized adaptive event-triggered (AET) scheme. Firstly, a new decentralized AET scheme is proposed, and some unnecessary data packets are discarded through decentralized adaptive rule, thereby saving network communication resources. Secondly, the H ∞ performance analysis of the filter error system is presented by using the fuzzy line-integral method, which does not need to give the time derivative upper bounds of the membership function in advance. Then, the combination of the Wirtinger-based inequality and the extended reciprocally convex matrix inequality is used to establish sufficient conditions for the filter error system to meet H ∞ performance. Moreover, a method for jointly designing the distributed AET parameters and fuzzy filter parameters is proposed. Finally, two examples are given to verify the effectiveness of the proposed method.